Kepemimpinan Digital Dalam Membentuk Budaya Organisasi Bank Syariah Indonesia ( BSI ) landmark Kota Banda Aceh - Presilawati, Febyolla; Abian, Muhammad; Qabri, Muhammad (Jurnal Bisnis Digital, 2024)
This research aims to analyze the role of digital leadership in shaping organizational culture at BSI Landmark Banda Aceh City. Considering the importance of leadership in the digital era, this research focuses on how technology and digital-based leadership can create an efficient and adaptive work culture. The method used is qualitative research with a case study approach, which involves interviews with several leaders and staff at BSI Landmark. The research results show that digital leadership has a significant role in strengthening communication, increasing team collaboration, and creating organizational cultural values that are more open and responsive to change. This research concludes that the application of technology in leadership can be the key to forming a more productive and innovative organizational culture.